2021
DOI: 10.1136/thoraxjnl-2020-216370
|View full text |Cite
|
Sign up to set email alerts
|

Role of extracellular vesicles in chronic lung disease

Abstract: To explore the role of extracellular vesicles (EVs) in chronic lung diseases.EVs are emerging as mediators of intercellular communication and possible diagnostic markers of disease. EVs harbour cargo molecules including RNA, lipids and proteins that they transfer to recipient cells. EVs are intercellular communicators within the lung microenvironment. Due to their disease-specific cargoes, EVs have the promise to be all-in-one complex multimodal biomarkers. EVs also have potential as drug carriers in chronic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 152 publications
0
19
0
1
Order By: Relevance
“…Thymic stromal lymphopoietin (TSLP), thymus and activated chemokine (TARC), and IL-8 had also been used in the diagnosis of antifungal treatment of patients with asthma-induced ABPA ( Kozlova et al, 2020 ). In addition, extracellular vesicles (EVs), one kind of novel intercellular transporter, had also been confirmed in the role of diagnostic value in COPD, cystic fibrosis (CF), asthma, and lung cancer ( Trappe et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thymic stromal lymphopoietin (TSLP), thymus and activated chemokine (TARC), and IL-8 had also been used in the diagnosis of antifungal treatment of patients with asthma-induced ABPA ( Kozlova et al, 2020 ). In addition, extracellular vesicles (EVs), one kind of novel intercellular transporter, had also been confirmed in the role of diagnostic value in COPD, cystic fibrosis (CF), asthma, and lung cancer ( Trappe et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…As discussed above, cellular communication is of major importance in IPF, and part of this communication is mediated through EVs [ 201 , 202 ]. There is growing interest regarding the use of EVs isolated from anti-inflammatory and anti-fibrotic mesenchymal stem cells as a therapy for fibrotic disorders [ 203 , 204 ].…”
Section: Lipid-focused Therapiesmentioning
confidence: 99%
“…Clinically, EVs can be found and isolated from the majority of biological fluids, although blood and BALF are the most well-characterized sources of EVs ( 114 ). Increasing evidence has indicated that exosomes play a cardinal role in intercellular communication by delivering their shipments to target cells in the lungs (such as miRNAs).…”
Section: Role Of Exosomal Micrornas In Pulmonary Fibrosismentioning
confidence: 99%